Pine withering - causes and prospects for protection - Zaimenko, N.V.; Ellans’ka, N.E.; Ivanyts’ka, B.O.; Kharytonova, I.P.; Bedernichek, T.Y.; Yunosheva, O.P.; Shvartau, V.V.; Mykhalska, L.M. (Reports of the National Academy of Sciences of Ukraine, 2019)
The outecological factors of a negative influence on the adaptive potential of Pinus sylvestris L. plants have been determined. A significant increase in the content of ammonia nitrogen in the soil under dry pines has been detected on the experimental plot by monitoring the territory of the National Botanical Gardens. This is associated with the rapid destruction of forest litter, soil compaction, and the intensive development of grassy vegetation. In model experiments, we analyzed the effect of high positive temperatures on the accumulation of ammonia nitrogen forms and the growth of the number of ammonifiers in the soil. According to the results of studies, the differences in a growth of the N4+ concentration are consistent with the data on CO2 emissions from the soil surface. We propose the developments for improving the condition of pine plantations.